2023
DOI: 10.22367/jem.2023.45.01
|View full text |Cite
|
Sign up to set email alerts
|

The role of e-government in disaster management: A review of the literature

Abstract: Aim/purpose – Disasters or catastrophic events create unforeseen circumstances and require new approaches from local and national administrations in addressing the nega- tive impacts on society and the economy. Determining the role of e-government in providing the kind of services that are especially needed has become particularly rele- vant during COVID-19. This paper aims to assess the progress and current state of research on the role of e-government during or in the aftermath of catastrophic events. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Assuming public sector wants to produce a given and increased level of output and outcomes, increasing efficiency and productivity will enable this to be achieved with lesser resource or free resources that can be used to produce greater levels of service. Technology has had and will continue to have, a profound effect on increasing efficiency and productivity through improvements in rationality and restructuring (Roztocki et al, 2021).…”
Section: Part Three: the Technological And Technical Development Of P...mentioning
confidence: 99%
“…Assuming public sector wants to produce a given and increased level of output and outcomes, increasing efficiency and productivity will enable this to be achieved with lesser resource or free resources that can be used to produce greater levels of service. Technology has had and will continue to have, a profound effect on increasing efficiency and productivity through improvements in rationality and restructuring (Roztocki et al, 2021).…”
Section: Part Three: the Technological And Technical Development Of P...mentioning
confidence: 99%
“…Given the current reality of e-democracy, definitions of the phenomenon are diverse and, in some cases, biased. However, despite the recent nature of the phenomenon, it can be considered directly linked to and almost as an extension of the concept of egovernment, which has been around for several decades (Roztocki et al, 2023). Proof of this is that in the literature, you can find several terms to refer to this reality, such as e-democracy, e-government, e-participation, cyberpolitics, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a consequence of the global expansion of digital media and its benefits for political communication and government processes (Kneuer, 2016;Roztocki et al, 2023), it is increasingly evident how Information and Communication Technologies (ICTs) influence and will continue to influence political institutions (at different levels) and their relationship with citizens (Lidén, 2015;Sendag et al, 2022) in turbulent environments (Antón-Maraña et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In March 2011, Japan experienced the Great East Japan Earthquake, which underlined major problems with information and communication technology, especially in the Fukushima Daiichi nuclear power plant accident. Narcyz et al (2) reported the current landscape of research dealing with the role of e-government in disaster management, but no study has mentioned radiation disasters.…”
Section: Introductionmentioning
confidence: 99%